Attitudes and HRM decisions toward older workers in Africa: exploring contradictions through an empirical study - Rego, Arménio (2020)
We explored the attitudes toward older workers of African versus Portuguese managers, and how these managers make HRM decisions in scenarios involving younger versus older workers. To make cultural, social, and institutional explanations more robust, we also included two samples of students attending Portuguese universities: one sample comprising African students, the other comprising Portuguese ones. The main findings were: (a) a three-factor model (conscientiousness and performance; social capital and generosity; adaptability) of attitudes toward older workers emerged as satisfactory across the four samples; (b) in comparison with the Portuguese participants, African individuals expressed more positive attitudes toward older workers while, at the same time, discriminated against older workers more; (c) the findings were almost identical for both managers and students. Although African individuals showed more positive attitudes toward older workers than did the Portuguese, they made more discriminatory decisions in the HRM scenarios. We suggest that this contradiction may emerge from dualities characterizing Africa.